Performance-Based Optimum Design of Steel Frames by an Improved Quantum Particle Swarm Optimization. Issue 2 (February 2014) - Gholizadeh, Saeed; Moghadas, Reza Kamyab
The main aim of this work is to present a methodology for performance-based optimum seismic design of moment resisting steel frame structures. In the present study, an improved quantum particle swarm optimization (IQPSO) metaheuristic algorithm is proposed to implement performance-based optimum design (PBOD) process. During the optimization process, QPSO and IQPSO algorithms minimize the structural weight subject to performance constraints on inter-story drift ratios based on FEMA-356 provisions at the immediate occupancy (IO), life safety (LS) and collapse prevention (CP) performance levels. Nonlinear pushover analysis is conducted to compute the necessary structural responses during the PBOD process. Two numerical examples are presented to illustrate the efficiency of the presented methodology. The numerical results demonstrate the superiority of the proposed IQPSO to the classical QPSO algorithm.